2016
DOI: 10.1002/hpm.2356
|View full text |Cite
|
Sign up to set email alerts
|

Where there is no policy: governing the posting and transfer of primary health care workers in Nigeria

Abstract: SummaryThe posting and transfer of health workers and managers receives little policy and research attention in global health. In Nigeria, there is no national policy on posting and transfer in the health sector. We sought to examine how the posting and transfer of frontline primary health care (PHC) workers is conducted in four states (Lagos, Benue, Nasarawa and Kaduna) across Nigeria, where public sector PHC facilities are usually the only form of formal health care service providers available in many commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…9 Abimbola et al adapted the multilevel framework developed by Ostrom 10 to assess governance of primary healthcare in Nigeria. [10][11][12][13] Furthermore, Abimbola et al used the concept of transaction costs originally developed by Williamson (1979) to explore the barriers to accessing tuberculosis services in Nigeria. 14 Other examples of institutional analysis can be found in our recent systematic review of frameworks for assessing health system governance.…”
Section: Introductionmentioning
confidence: 99%
“…9 Abimbola et al adapted the multilevel framework developed by Ostrom 10 to assess governance of primary healthcare in Nigeria. [10][11][12][13] Furthermore, Abimbola et al used the concept of transaction costs originally developed by Williamson (1979) to explore the barriers to accessing tuberculosis services in Nigeria. 14 Other examples of institutional analysis can be found in our recent systematic review of frameworks for assessing health system governance.…”
Section: Introductionmentioning
confidence: 99%
“…However, most efforts to address them have focused on increasing their numbers and distribution, particularly Community Health Extension Workers 44. This approach is not unusual in LMICs given that maldistribution and high attrition rates are common human resource challenges in these countries 45. For example, maldistribution of health workers following punitive transfers and lobbying for posting are common concerns that have affected equitable access of clients to services in India, Pakistan, Mali and Kenya, which staff audits and re-distribution have attempted to solve 33–36.…”
Section: Discussionmentioning
confidence: 99%
“…Abimbola et al's study in Nigeria reported that HRH management decisions in the health service were sometimes based on requests for favours from health workers and politicians. In addition, lobbying powerful political intermediaries could be used by health workers to reverse a decision they deemed unfavourable [37]. Karakose's study in Turkey interviewed doctors on their views on favouritism and reported that unfairness in appointing managers based on their political and ideological views was common [38].…”
Section: Patronage and Clientelismmentioning
confidence: 99%
“…Cronyism means, 'the appointment of friends and associates to positions of authority, without proper regard to their qualifications,' [42]. Studies that have considered nepotism and cronyism in the health sector include Abimbola's study on Nigeria referred to above, which reported that Senior Medical Personnel personalized appointments outside formal procedures and without clear criteria, 'because of gratitude or friendship' [37]. This sometimes resulted in the recruitment of persons who displayed signs of incompetency.…”
Section: Nepotism and Cronyismmentioning
confidence: 99%